Perancangan Ulang UI dan UX Website Rumah Bersalin Cuma Cuma untuk Calon Donatur di Kota Bandung - Diwan Setiawan; Faiz Firmansyah; Nichi Hana Karlina (Universitas Informatika dan Bisnis Indonesia, 2024)
Rumah Bersalin Cuma Cuma, or commonly called Free Maternity Home, is a health institution that provides childbirth and other health services free of charge to mothers and children from poor communities. Founded in 2004 with ZISWaf funding support, this maternity home is committed to providing safe and comfortable births for poor mothers. In an effort to improve service and affordability, Rumah Bersalin Cuma Cuma launched a website. This website is a means to raise donations online and provide information to the public about the programs run by the maternity home. This website redesign was carried out to improve the user interface and user experience which was less attractive and informative. Methods such as interviews, observations, and questionnaires are used to understand the problems faced by users when using the Rumah Bersalin Cuma Cuma website. With this redesign, it is hoped that the image of Rumah Bersalin Cuma Cuma can be improved and increase satisfaction and positive assessments from users of the website.